Implementasi Structured System Analysis and Design Method pada Sistem Informasi Retribusi Pasar - Aqil, Moh. Aqil Mukhtar Alfarera; Susanto, Adi (Universitas Boyolali, 2024)
Mojopanggung market is a traditional market located in mojopanggung sub-district, giri sub-district, banyuwangi regency. Based on the field survey, there are problems with the data processing system for market retribution income reports managed by market treasurers who stell have a conventional approach in processing payment data recorded in books and microsoft excel. This results in the current system having many weaknesses and limitations, increasing the risk of data loss. In addition, providing information to recapitulation officers in the field of market management becomes difficult. Therefore, it is necessary to design a website-based market levy income information system, which can handle problems that arise, where the system can be used to monitor market levy income report data, as well as facilitate the provision of information to recapitulation officers in the field of market management the design of a website-based market levy income information system was built by applying the structured system analysis and design method (SSADM). From the results of research that has been carried out, every company or government agency is encouraged to utilize information technology as a means of supporting business activities. A part from that, designing a website-based market levy income information system is very necessary and needed, in order to make it easier to provide information related to market traders’ dependents, as well as reporting levy income results and activities for monitoring data, so that in can produce levy income report data more easily and effectively